Oggetti personali ed emozioni: il caso degli artefatti affettivi - Piredda, Giulia (Rivista Italiana di Filosofia del Linguaggio, 2020)
In this paper I would like to elaborate the idea of “affective artifact”, framing it in the landscape of situated affectivity (Piredda 2019). Affective artifacts work in the domain of affectivity like cognitive artifacts do in our cognitive life: they sustain, help and transform affective processes and experiences, through the interaction between them and the agent. After having introduced and discussed the idea of affective artifacts, I will propose some elements for their classification and compare it with similar notions, like evocative objects (Heersmink 2018; Turkle 2007) and affective scaffolds (Colombetti, Krueger 2015). Lastly, I will consider some possible criticisms and propose some potential further developments.